From Leadership Training to Service Improvement: A Literature Review on Training Transfer, Change Projects, and Administrative Capacity in Tambrauw Regency Government - Yacoba Tabita Kinho; Amirul Mustofa; Sedarmayanti Sedarmayanti; Dian Ferriswara (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Leadership training has become a key instrument in public sector reform, driven by expectations that public managers act as strategic leaders to improve organizational performance and public service delivery. However, despite substantial investments, public administration research consistently highlights a gap between leadership training participation and tangible service improvements, particularly in resource-constrained local governments. Existing studies often examine leadership training effectiveness, training transfer, organizational change, and administrative capacity separately, resulting in limited integration across these interconnected processes. This fragmentation restricts understanding of how leadership competencies gained through training are transferred into practice, institutionalized through post-training change initiatives (Aksi Perubahan), and translated into sustainable administrative capacity and service outcomes. To address this gap, this integrative literature review synthesizes and critically analyzes peer-reviewed research on public sector leadership training, focusing on training transfer mechanisms, action-based change initiatives, and administrative capacity development in local governments, using the Tambrauw Regency Government as an illustrative context. The review draws on articles indexed in Scopus, Web of Science, and Google Scholar published between 2016 and 2025, selected based on public sector relevance and theoretical rigor. Using thematic synthesis and conceptual mapping, the findings show that leadership training contributes to service improvement only when supported by a conducive transfer climate, strong organizational commitment, and structured change projects. These change initiatives mediate the transformation of individual competencies into organizational routines, while administrative capacity determines the sustainability of outcomes. The study contributes to administrative capacity theory and provides practical insights for designing effective leadership training policies in peripheral local government contexts.